Noncombustible Schools for Omaha - Alsmeyer, William C. (Engineering Journal, 1971)
Code restrictions on types of construction and fire resistance requirements can have a significant effect on the cost of a building. Sometimes these restrictions are arbitrary and unnecessary, and result in higher costs without any increase in public safety or protection of property. Unduly restrictive fire protection requirements have a particularly severe impact on the cost of steel construction. However, logical code changes can be achieved through the cooperative efforts of designers and building officials. A few years ago the authors firm participated in a successful effort to amend the Omaha Building Code to permit the use of unprotected non-combustible construction, such as steel, for most school facilities. The following description of this experience is presented in the hope that it will encourage others to work for the elimination of unduly restrictive fire protection requirements throughout the country.